Influence of minor tensile stress on the oxidation behavior of powder metallurgy superalloy. (September 2022) - Ye, Xianjue; Yang, Biaobiao; Liu, Jiantao; Lai, Ruilin; Li, Yunping
Abstract: Oxidation behavior of a novel powder metallurgy superalloy was investigated at 900 °C under minor tension of 0, 30, 50, and 70 MPa, respectively. Minor tensile stress was proved helpful in enhancing the oxidation resistance of superalloy. With increasing stress, oxide scale became thinner, more compact, more continuous and flatter. This was also accompanied by a reduced internal oxidation in alloy matrix. At the same time, more Ti was accumulated into the interior of Cr2 O3 layer than in its surface, due to the inhibited outward diffusion of Ti by the more compact oxide scale at higher tensile stress. Highlights: Oxidation of superalloy under tension of 0-70 MPa was studied. Tension is helpful in enhancing oxidation resistance. Oxide scales is thinner, more compact and flatter with increasing stress. Internal oxidation is reduced at higher stress. Increased content of Ti in Cr2 O3 with increasing stress.